Are wall thickness channels defined by computed tomography predictive of isthmuses of postinfarction ventricular tachycardia? - Takigawa, Masateru; Duchateau, Josselin; Sacher, Frederic; Martin, Ruairidh; Vlachos, Konstantinos; Kitamura, Takeshi; Sermesant, Maxime; Cedilnik, Nicolas; Cheniti, Ghassen; Frontera, Antonio; Thompson, Nathaniel; Martin, Calire; et al. (Heart rhythm, 2019)
Wall thickness (WT) in post-myocardial infarction scar is heterogenous, with channels of relatively preserved thickness bordered by thinner scar. This study sought to determine whether 3-dimensionally-reconstructed computed tomography (CT) channels correlate with electrophysiological isthmuses during ventricular tachycardia (VT). We retrospectively studied 9 postinfarction patients (aged 57 ± 15 years, 1 female) with 10 complete VT activation maps (cycle length 429 ± 77ms) created using high-resolution mapping. Three-dimensionally-reconstructed WT maps from CT were merged with the activation map during sinus rhythm (SR) and VT. The relationship between WT and electrophysiological characteristics was analyzed. A total of 41 CT channels were identified (median 4 per patient), of median (range) length 21.2 mm (17.3-36.8 mm), width 9.0 mm (6.7-16.5 mm), and area 1.49 cm (1.00-1.75 cm ). WT in the channel was significantly thicker in the center than in the edge (median 2.4 mm vs 1.5 mm, P < .0001). Of 3163 (2493-5960) mapping points in SR, 382 (191-1115) local abnormal ventricular activities (LAVAs) were identified. One patient had a maximal proportion of LAVAs in 3-4 mm, 3 patients in 2-3 mm, 2 in 1-2 mm, and 2 in 0-1 mm. The VT isthmuses of all 10 VTs corresponded with 1-4 CT channels. Twenty-one of the 41 CT channels (51.2%) corresponded to a VT isthmus (entrance, mid, or exit). Electrophysiological VT isthmuses were more likely to be associated with CT channels that were longer (P = .04, odds ratio [OR] 1.05/mm), thinner (but not less than 1 mm) (P = .03, OR 0.36/mm), or parallel to the mitral annulus (P = .07, OR 3.93). VT isthmuses were always found in CT channels (100% sensitivity), and half of CT channels hosted VT isthmuses (positive predictive value 51%). Longer and thinner (but >1 mm) CT channels were significantly associated with VT isthmuses.